CX‐ASAP: a high‐throughput tool for the serial refinement and analysis of crystallographic data collected under varying conditions. Issue 2 (28th February 2023) - Thompson, Amy J.; Smith, Kate M. L.; Clegg, Jack K.; Price, Jason R.
Abstract : CX‐ASAP is a new open‐source software project designed to greatly reduce the time required to analyse crystallographic data collected under varying conditions. This software will allow the rapid refinement and finalization of dynamic crystallographic experiments. Abstract : CX‐ASAP is a new open‐source software project designed to greatly reduce the time required to analyse crystallographic data collected under varying conditions. Scripted in Python3, CX‐ASAP can automatically refine, finalize and analyse data collections with wide‐ranging temperatures, pressures etc . This is achieved using a reference structure, allowing for quick identification of problems, phase changes and even model comparison. The modular design means that new features and customized scripts can be easily added, tailoring the capabilities to the specific needs of the user. It is envisioned that CX‐ASAP will help to close the growing gap between fast collection times and slow data finalization.